MiR-155-5p antagonizes the apoptotic effect of bufalin in triple-negative breast cancer cells. Issue 1 (January 2016) - Wang, Qian; Li, Ce; Zhu, Zhitu; Teng, Yuee; Che, Xiaofang; Wang, Yan; Ma, Yanju; Wang, Yiding; Zheng, Huachuan; Liu, Yunpeng; Qu, Xiujuan
Abstract : Bufalin, a cardiotonic steroid isolated from toad venom, has been shown to kill various types of tumor cells. Our previous study showed that triple-negative breast cancer (TNBC) cells were less sensitive to bufalin than other types of breast cancer cells, but the reason for this lower sensitivity remains unclear. In this study, we showed that bufalin induced apoptosis in MDA-MB-231 and MCF-7/ADR TNBC cell lines, accompanied by increased miR-155-5p expression. Overexpression of miR-155-5p promoted proliferation and reduced bufalin-induced apoptosis of TNBC cells. In contrast, downregulation of miR-155-5p increased sensitivity to bufalin and upregulated the expression of FOXO3A. Bufalin also downregulated DNA methyltransferases 1 and 3a (DNMT1 and DNMT3a), and concurrent inhibition of DNMT1 and DNMT3a significantly increased miR-155-5p expression. These results indicate that miR-155-5p antagonizes bufalin sensitivity in TNBC cells, and that downregulation of DNMT1 and DNMT3a may be responsible for the bufalin-induced upregulation of miR-155-5p. Abstract : Supplemental Digital Content is available in the text.